2016
DOI: 10.1101/074476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Na-Dene populations descend from the Paleo-Eskimo migration into America

Abstract: Prehistory of Native Americans of the Na-Dene language family remains controversial. Genetic continuity of Paleo-Eskimos (Saqqaq and Dorset cultures) and Na-Dene was proposed under the three-wave model of America's settlement; however, recent studies have produced conflicting results. Here, we performed reconstruction and dating of Na-Dene population history, using genome sequencing data and a coalescent method relying on rare alleles (Rarecoal). We also applied model-free approaches for analysis of rare allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Q-M25 is observed from Eastern Europe until Central Asia with its highest frequency in the Iranian Plateau where it is virtually only represented by its clade Q-L712 (Additional file 9: Figure S3c). This lineage has not been observed in present-day North Native Americans, but it has been recently reported in ancient Aleutian Islanders, ancient northern Athabaskans and in a 4250-year-old individual of the Chukotkan Ust’-Belaya culture [33].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Q-M25 is observed from Eastern Europe until Central Asia with its highest frequency in the Iranian Plateau where it is virtually only represented by its clade Q-L712 (Additional file 9: Figure S3c). This lineage has not been observed in present-day North Native Americans, but it has been recently reported in ancient Aleutian Islanders, ancient northern Athabaskans and in a 4250-year-old individual of the Chukotkan Ust’-Belaya culture [33].…”
Section: Resultsmentioning
confidence: 94%
“…3B). Indeed Q-M25, which is frequent in modern Western Eurasians [53, 54], is described as Q-L712 and Q-L713 in ancient samples from the Beringian area [33] indicating that, during the warmer mid-Holocene period, populations carrying different haplogroup Q lineages reached the former Beringian area but gave a limited contribution to the modern Y chromosome gene pool. Differently, Q-F746 , which is common in Southeast Asia as Q-M120 (4.6 ± 0.9 ky), encompasses the pre-M120 lineage (dated 14.7 ± 2.3 ky) observed in an Alaskan subject (Tsimshian), the Q-B143 lineage (8.4 ± 1.3 ky), which characterizes the Saqqaq Paleo-Eskimo (4 ky), and the new branch Q-PV706 (2.8 ± 0.9 ky) observed in a few Koryaks of Northeastern Siberia.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative, that NNAs and SNAs split in Alaska, seems less likely; it would have required several thousand years of strong population structure prior to ~16 ka ago to differentiate those groups from each other and from ABs, as well as a separate SNA presence, which has yet to be found (1). These data indicate that the Athabascans and Inuit, who inhabit Alaska today and are NNAs but with additional Siberianrelated ancestry (1,4,18,33), presumably moved north into the region sometime after ~9 ka ago, the age of the Trail Creek individual (1,13).…”
Section: Insights Into Early Eastern Beringian Populations From An Al...mentioning
confidence: 92%
“…Pacific Northwest groups had a Late Pleistocene demographic history argued to be distinct from that of early SNA groups (1,2,9,18,33). To explore the population history and the relationship of regional populations to NNAs and SNAs, we assessed the genetic affinities between the 5.6-kaold Big Bar Lake individual from the Fraser Plateau of central British Columbia and other NAs.…”
Section: Long-term Complex Population History In the Pacific Northwestmentioning
confidence: 99%
“…The heuristic approach in TreeMix 24 showed that the best proxies for the Asian component in Athabascans and Greenlandic Inuit are Koryaks and the Saqqaq individual, respectively. We then followed an incremental approach for fitting an f-statistic-based admixture graph 20 , including the Kets, previously suggested to share a linguistic and perhaps a genetic link with Athabascans 11,27 . This approach recapitulated the TreeMix results , and yielded a model in which both Athabascans and Greenlandic Inuit derive from the NNA branch.…”
mentioning
confidence: 99%